The Human Significance and the Whole. Theological Readings and Affiliations in Freud and Lacan - Cardoso, Joaquín (2018)
The question of human significance and the whole knew a philosophical course so vast that it did not exempt even "atheist" thinkers, like the historical materialists or the parents of psychoanalysis. Although their objectives were different, the genealogy of their readings and their respective intellectual debts allow us to locate within the theological framework many aspects of their theoretical practice. For this reason, the following article will be the first of some works aimed at identifying the influence of religion and theology on authors linked to the eminently secular thought of the twentieth century. From this same perspective, we seek to locate the question for the One and for the All at the center of dialectical philosophy, for which we take as an excuse the book "Grace and desire. San Agustin, Pascal, Lacan" by Sara Vassallo.